High prevalence of sarcopenia and myosteatosis in patients undergoing hemodialysis - Fu, Chen; Yan, Dong; Wang, Ling; Duan, Fangfang; Gu, Dalong; Yao, Ning; Sun, Mingke; Wang, Di; Lin, Xuya; Wu, Yanglei; Wang, Xiaofei; Cheng, Xiaoguang; et al. (Frontiers in Endocrinology, 2023)
Background and Purpose: Sarcopenia is highly prevalent (28.5–40.3%) in patients undergoing hemodialysis and leads to poor clinical outcomes. However, the association between muscle quality and sarcopenia in patients receiving hemodialysis remains unclear. Therefore, we aimed to explore the association between muscle cross-sectional area (CSA) and proton-density fat-fraction (PDFF) in patients with sarcopenia undergoing hemodialysis. Methods: Seventy-six patients undergoing hemodialysis for > 3 months were enrolled. Their handgrip strength (HGS), short physical performance battery (SPPB) performance, and appendicular skeletal muscle mass index (ASMI) were measured. Sarcopenia was defined using the Asian Working Group for Sarcopenia 2019 consensus update. All patients underwent quantitative magnetic resonance imaging. CSA and PDFF were measured for the thigh, trunk, and gluteus muscles. Results: The prevalence of probable, confirmed, and severe sarcopenia in this study was 73.7%, 51.3%, and 22.4%, respectively. Older age (OR: 1.061, P < 0.003); lower body mass index (BMI) (OR: 0.837, P = 0.008), albumin (OR: 0.765, P = 0.004), prealbumin (OR: 0.987, P = 0.001), predialysis blood urea nitrogen (BUN) (OR: 0.842, P < 0.001), predialysis creatinine (OR: 0.993, P < 0.001), phosphorus (OR: 0.396, P = 0.047); lower CSA of the thigh (OR: 0.58, P = 0.035), third lumbar (L3) trunk (OR: 0.37, P = 0.004), gluteus minimus and medius (OR: 0.28, P = 0.001), and gluteus maximus (OR: 0.28, P= 0.001); and higher PDFF of the thigh (OR: 1.89, P = 0.036) and L3 trunk (OR: 1.71, P = 0.040) were identified as sarcopenia risk factors. The gluteus minimus and medius CSA was lower in patients with sarcopenia than in those without after adjusting for age and BMI (OR: 0.37, P = 0.017). Higher thigh (P = 0.031) and L3 trunk (P = 0.006) muscle PDFF were significantly associated with lower HGS. Furthermore, higher thigh (P = 0.011) and L3 trunk (P = 0.010) muscle PDFF were also inversely correlated with lower ASMI. Conclusions: Our findings demonstrate the high prevalence of sarcopenia and myosteatosis in patients undergoing hemodialysis and might trigger a paradigm shift in intervention strategies for patients receiving hemodialysis.